Dicrostonyx nelsoni Merriam 1900 - Guy G. Musser; Michael D. Carleton (Smithsonian Institution Press, 1993)
Dicrostonyx nelsoni Merriam, 1900. Proc. Washington Acad. Sci., 2:25. TYPE LOCALITY: USA, Alaska, Norton Sound, St. Michael. DISTRIBUTION: W Alaska and Alaskan Peninsula, USA. SYNONYMS: peninsulae. Published as part of Guy G. Musser & Michael D. Carleton, 1993, Order Rodentia - Family Muridae, pp. 501-755 in Mammal Species of the World (2 nd Edition), Washington and London :Smithsonian Institution Press on page 510, DOI: 10.5281/zenodo.7353098